Estudio del comportamiento del consumidor de la compra de materiales de construcción en la ciudad de Machala - Paladines Cabrera, Estefania Carolina (2015)
Was developed with the purpose of determining the behavior of consumers in the purchase of building materials in the City of Machala through research, data collection and analysis for knowing the tastes, preferences and the degree of acceptance of the current and potential consumers. In which was used the theories of reference such as concept, behavior and consumer satisfaction, perspective about how consumers will perceive the construction materials to build or rebuild their homes. The methodology that was used was the survey model that ran to the owners of the stores in the city already mentioned. Within the research executed it was determined that the brands that is sold is more Edessa, and Holcim Ecuaceramica; because these are time consuming in the market, so it turned out that the same expectations that lead to use the purchase is that they can increase their sales and that this in turn allows them to gain market share, the expectations at the time of purchasing materials for the construction mentioned that it is good material and have ease of payment, they also indicated that the manufacturers is the channel of distribution that you buy those products. In conclusion, the implementation of the marketing plan brings that thanks to the tool of the CRM or database this will help the owners of the company have direct contact with customers, which can be seen satisfied by the products that they buy and with the online marketing will help the company attract publicity through social networks, exposing all about their materials such as: promotions, offers or discounts. It is recommended that the owners of the stores be able to obtain a good corporate image which will benefit in a positive manner to the business.